Propuesta de un modelo de negocio para la creación de una granja avícola en la parroquia Nambacola, cantón Gonzanamá, basándose en otros modelos relacionados - Herrera Ruiz, Auria Maribel (2024)
Being aware that poultry farming is one of the main economic activities of the country's agricultural sector, which currently contributes 3% of the GDP, its value chain is broad from which producers of corn, soybeans, transporters, merchants and the final consumer. In the present research work carried out, various feasibility studies are shown, which yield positive results on the implementation of this type of microenterprise, which coincide with the general objective set out in this study, "Propose a business model for poultry farms." destined for the production of Creole eggs in the Nambacola parish, Gonzanamá canton, based on other business models developed for the sector", the study was carried out, with a qualitative and quantitative approach, taking as reference a sample size of 384 people to whom a survey was applied and it was determined that there is an unsatisfied demand of 137,804 units for the first year, and the investment cost to implement the poultry farm is $52,986.15; In order to generate profits, the product must be sold at a price of $7.48 per bucket of 30 eggs. Analyzing the profitability on the total investment, it gives us a positive NPV of 38,788.45. The IRR is 33.49%, a figure higher than the existing financial rates in the banking market, making the project executable. The Benefit / Cost ratio is 1.57 positive indicator, the capital recovery period is 2 years, 9 months and 26 days, the sensitivity analysis of the project has an increase in its costs of 7% and with the decrease in income of 4.5%. With these results, it can be stated that the implementation of this business model is completely feasible if it adjusts to the established guidelines.